Linking environmental psychology and critical social psychology: Theoretical considerations toward a comprehensive research agenda - Kühn, Thomas; Bobeth, Sebastian (Frontiers in Psychology, 2022)
In order to foster pro-environmental behavior in the midst of a global ecological crisis, current research in environmental psychology is often limited to individual-related factors and theories about conscious processing. However, in recent years, we observe a certain discontentment with the limitations of this approach within the community as well as increasing efforts towards broadening the scope (e.g., promotions of collective and social identity processes). In our work, we aim for a closer investigation of the relations between individuals, societal factors, and pro-environmental actions while considering the role of the unconscious. We hereby draw on the work of critical social psychology (CSP). From a life course perspective, we emphasize the important role of socialization, institutional and cultural contexts for mindsets and related perceptions, decisions and actions. This link between the individual and the society enables us to understand biographical trajectories and related ideologies dominant within a society. We seek to show that the approach of CSP is helpful for understanding why efforts of establishing pro-environmental actions on a large scale are still failing. In this article, we discuss the theoretical links between environmental psychology and CSP as well as possible implications, paving the way for a comprehensive future research agenda.